Chronic lung disease in HIV-infected children established on antiretroviral therapy. (28th November 2016) - Rylance, Jamie; Mchugh, Grace; Metcalfe, John; Mujuru, Hilda; Nathoo, Kusum; Wilmore, Stephanie; Rowland-Jones, Sarah; Majonga, Edith; Kranzer, Katharina; Ferrand, Rashida A
Abstract : Objective: Respiratory disease is a major cause of morbidity and mortality in HIV-infected children. Despite antiretroviral therapy (ART), children suffer chronic symptoms. We investigated symptom prevalence, lung function and exercise capacity among older children established on ART and an age-matched HIV-uninfected group. Design: A cross-sectional study in Zimbabwe of HIV-infected children aged 6–16 years receiving ART for over 6 months and HIV-uninfected children attending primary health clinics from the same area. Methods: Standardized questionnaire, spirometry, incremental shuttle walk testing, CD4 + cell count, HIV viral load and sputum culture for tuberculosis were performed. Results: A total of 202 HIV-infected and 150 uninfected participants (median age 11.1 years in each group) were recruited. Median age at HIV diagnosis and ART initiation was 5.5 (interquartile range 2.8–7.5) and 6.1 (interquartile range 3.6–8.4) years, respectively. Median CD4 + cell count was 726 cells/μl, and 79% had HIV viral load less than 400 copies/ml. Chronic respiratory symptoms were rare in HIV-uninfected children [ n  = 1 (0.7%)], but common in HIV-infected participants [51 (25%)], especially cough [30 (15%)] and dyspnoea [30 (15%)]. HIV-infected participants were more commonly previously treated for tuberculosis [76 (38%) vs 1 (0.7%), P  < 0.001], had lower exercise capacity (mean incremental shuttle walk testing distance 771 vs 889 m, respectively, P  < 0.001) and more frequently abnormal spirometry [43 (24.3%) vs 15 (11.5%), P  = 0.003] compared with HIV-uninfected participants. HIV diagnosis at an older age was associated with lung function abnormality ( P  = 0.025). No participant tested positive for Mycobacterium tuberculosis . Conclusion: In children, despite ART, HIV is associated with significant respiratory symptoms and functional impairment. Understanding pathogenesis is key, as new treatment strategies are urgently required. Abstract : Supplemental Digital Content is available in the text